Algorithms ESA 2013 21st Annual European Symposium, Sophia Antipolis, France, September 2-4, 2013. Proceedings - Bodlaender, Hans L.; Italiano, Giuseppe F. (Lecture Notes in Computer Science,, 2013)
This book constitutes the refereed proceedings of the 21st Annual European Symposium on Algorithms, ESA 2013, held in Sophia Antipolis, France, in September 2013 in the context of the combined conference ALGO 2013. The 69 revised full papers presented were carefully reviewed and selected from 303 initial submissions: 53 out of 229 in track "Design and Analysis" and 16 out of 74 in track "Engineering and Applications". The papers in this book present original research in all areas of algorithmic research, including but not limited to: algorithm engineering; algorithmic aspects of networks; algorithmic game theory; approximation algorithms; computational biology; computational finance; computational geometry; combinatorial optimization; data compression; data structures; databases and information retrieval; distributed and parallel computing; graph algorithms; hierarchical memories; heuristics and meta-heuristics; mathematical programming; mobile computing; on-line algorithms; parameterized complexity; pattern matching; quantum computing; randomized algorithms; scheduling and resource allocation problems; streaming algorithms.